Efforts to Improve Learning Outcomes Using Cooperative Integrated Reading Models and Composition in Javanese Language Subjects Character Profile Material - Widowati, Dyah Sukmo (Universitas Nusantara PGRI Kediri, 2019)
The process of learning the Javanese Language in class VII A of SMPN 3 Kediri experienced problems especially with the use of learning methods. During this time the teacher only used the lecture method in teaching and learning activities (KBM). This lecture method places the teacher as the only source of learning, making students unable to use their abilities optimally. This causes the low learning outcomes of students who only as much as 38% of students who have complete KKM scores. The purpose of this study was to determine the improvement in learning outcomes of students of class VII A of SMPN 3 Kediri in the Odd Semester Academic Year 2018/2019 in Language lessons. Java material Figure Profile through Learning Methods Cooperative Integrated Reading and Composition. To achieve this goal used the method of classroom action research. The results of the study showed that pre-cycle starts 9 students complete with an average value of 69.6 and the percentage of success indicators of 38% of students complete KKM. Cycle 1 there were 13 study students completed with an average supply of 75.4 and the percentage of success indicators as much as 54% of students completed KKM. Cycle 2 shows 19 students complete with an average value of 82.5 and a success indicator of 79% of students complete KKM. Thus the Cooperative Integrated Reading and Composition learning method can improve the learning outcomes of VIIA students in SMP 3 Kediri in the odd semester of the school year 2018/2019 in Javanese Language Study material in the Profile.